A Contrastive Analysis of Linguistic Features of the Adjective“Black” in English and “Den” in Vietnamese - Phan Thị Lệ Huyền (2011)
This paper is a contrastive analysis of linguistic features of the adjective Black in English and Đen in Vietnamese. For observation and analysis, the data of 300 adjectives Black and 300 adjectives Đen as well as 300 samples ….